Portraying Arica’S Nursing in the Mid-Twentieth Century, Chile, 1950 [Retratando a Enfermagem Arica de Meados Do Século Xx. Chile, 1950 [Retratando la Enfermería Ariqueña de Mediados del Siglo Xx. Chile, 1950 - Castillo-Lobos, L; Nunez-Carrasco, E (Universidad de Santander, 2022)
Introduction: In the mid-twentieth century, the city of Arica experienced socio-political changes that led to a precarious social and health situation. During this time, Iris Veliz was the first professional nurse in the city, and her arrival was the starting point for the professionalization of nursing in the extreme north of Chile. Objective: To highlight through the person of Iris Veliz the trajectory of an anonymous Chilean nurse who has been written about incipiently. Materials and methods: Qualitative and socio-historical study, its findings emerged from secondary documentary sources and from the accounts of those who were part of Iris Veliz’s work team at the Juan Noé Hospital in Arica. Results: The findings were subjected to Flick’s thematic analysis and interpreted in light of Nancy Fraser’s epistemological premises regarding women’s recognition. Discussion: She is remembered in a positive way; however, her professional performance is made invisible because her field of action was a space of daily practices traditionally associated with women, which perpetuated her into a state of subjugation as a result of the regional exaltation of a dominant medical figure. Conclusions: Iris Veliz is an exponent of those nursing professionals who remain hidden in the restricted space of their actions and urges us to reflect on the anonymity of history as a disruptor of the culture of care. © 2022 Universidad de Santander. All Rights Reserved.